Pengurangan Hasil Tangkapan Pada Alat Tangkap Togok dengan Menggunakan BRD (Bycatch Reduction Device) Tipe Rope BRD di Kuala Tungkal, Provinsi Jambi - Muhamad Mauliddin; Romie Jhonnerie; Nofrizal Nofrizal (Universitas Riau, 2022)
Togok is a fishing gear in the form of a conical net body whose arms are on two poles and the success of catching it relies on currents, togok fishing gear is used to catch Rebon shrimp (Acetes japonicas) but in its operation, many catches are found bycatch. The high bycatch will have an impact on capture sustainable fisheries, one of the efforts to reduce bycatch is by using BRD (Bycatch Reduction Devices), the use of BRD has been widely carried out on trawl fishing gear but on togok fishing gear, it has never been done. This study aimed for knowing the reduction in catches of main catch, bycatch, and discard the togok fishing gear that has been installed with rope BRD and knows the reduction in catches of shrimp and fish species. This study uses experimental fishing, namely by carrying out direct fishing operations with local fishermen for 20 days of catch. The reduction of togok catch using BRD type rope BRD in the main catch is 8.4%, in bycatch is 11.8% and discard is 17, 1% and the reduction in catch of shrimp species ranged from 8,4% - 13,5% and reduction in catch of fish species ranged from 10,9% - 22,6%.